KAPASITAS PERKEMBANGAN KEMAMPUAN MOTORIK PADA ANAK USIA TAMAN KANAK-KANAK - Ahadin Ahadin (Jurnal Pesona Dasar, 2019)
Motor ability is an individual capacity to develop the ability of the skills that are possessed in an effort to heighten or accelerate the mastery of a skill. Individual capacities that are motor capability consist of: speed (speed), agility, power, balance (balance), flexibility (flexibility), and coordination (coordination). Motor development is a change in motor behaviour that occurs because of maturity and child interaction with the environment. Maturity is a change that occurs in the body within a period of time. While the environment consists of: family, friends play, and community environment. The function of motor capability for children in kindergarten is to promote labor, facilitate, accelerate in the mastery of various motor skills studied. Motor skills are a child's ability to display or demonstrate a skill. Motor capability occurs or is acquired through an integrated or associated process along with an exercise or enhancement through experience. Motor capability will occur with a change from time to time relatively permanent in the capacity to showcase a skilled motor skill.